The mountain story - Lansens, Lori (Simon & Schuster, 2015)
"A harrowing survival story about four strangers who spend five days lost in the mountain wilderness above Palm Springs. Four go up the mountain, but only three will come down... On the morning of Wolf Truly's eighteenth birthday, he boards the first cable car to head up the mountains just a few miles from his sun-bleached trailer home in the desert community outside of Palm Springs. Armed with nothing but the clothes on his back, Wolf's intention that morning was to give up on life--specifically at the mountain site of his best friend's tragic accident one year ago. But on that shaky ride up the mountain, fate intervenes and Wolf meets three women that will leave an indelible imprint on the rest of his life. Through a series of missteps, the four wind up lost and stranded among the forested cliffs--in sight of the desert city below, but unable to find a way down. As the days pass without rescue, we come to learn how each of them came to be on the mountain that morning. And as their situation shifts from misadventure to nightmare, the lost hikers forge an inextricable bond, pushing themselves, and each other, beyond their limits. Reminiscent of John Krakauer's modern classic Into the Wild and Cheryl Strayed's Wild, Lori Lansen's The Mountain Story is a deeply affecting novel that pays homage to the rugged beauty--and utterly unforgiving nature--of the wilderness, and considers the question: What price are you willing to pay not only for the ones you love, but for a complete stranger?"--